TINJAUAN YURIDIS PERJANJIAN KERJASAMA ANTARA PT. JAMSOSTEK (PERSERO) CABANG MEDAN DENGAN WADAH TENAGA KERJA LUAR HUBUNGAN KERJA (TK-LHK) BINAAN KANTOR PT. JAMSOSTEK (PERSERO) CABANG MEDAN - MEHAGA BASTANTA (University of North Sumatera, 2013)
ABSTRAK : Regulation of Labor and Transmigration Minister of Republic of Indonesia Number : Per-/24/Men/VI/2006 concerning the implementation program of Social Security for Labor outside job relation tells that social security program can do directly by each labor or coordinated by agent. Based on these condition, PT. Jamsostek (Persero) Branch of Medan makes a mutual agreement between PT. Jamsostek (Persero) and agent based by the purpose of title this writing. Writer concludes that the implementation of mutual agreement between TK-LHK and PT. Jamsostek (Persero) branch of Medan has implemented effectively. This was indicated by implementation of mutual agreement in which of 80 registered agents from May 2007 until October 2012, and just only 10 agents had been non active; dispute forms of mutual agreement or wanprestation by agents such as embezzlement of premium and not having goodwill of this mutual agreement; so forms of solution which are implemented by PT. Jamsostek (Persero) Branch of Medan are mutual deliberation and could be continued to the public court if both of parties are not agreement and do not extend the mutual agreement; mutual agreement could be ended by on the due date, by force majeure and both of parties agree to terminate the mutual agreement. Keywords : Mutual Agreement, TK-LHK, Jamsostek, Agent